The one hundred most-cited articles on laparoscopic liver surgery - Levi Sandri, Giovanni Battista; Gabriele Spoletini, Gabriele Spoletini (Laparoscopic Surgery, 2017)
Abstract: The aim of this review was to identify the 100 most-cited articles related to laparoscopic liver resection (LLR), to analyze their trend according to publication year and to summarize the knowledge and evidence these one-hundred articles brought to the surgical community. We performed a search to identify all studies dealing with LLR by utilizing the Institute for Scientific Information (ISI) Web of Science (Thomson Reuters, New York, NY, USA) database. We found 2,018 papers, applying the exclusion criteria on all articles, the 100 most cited articles on LLR were identified. The oldest article was published in 1996 and the most recent in 2015. The 100 articles were published in 23 different journals, 55 articles were published in 3 journals: Surgical Endoscopy [27], Annals of Surgery [20] and British Journal of Surgery [8]. The most frequent first and last authors were Dagher I (5 articles) and Cherqui D (7 articles) respectively. In 30 cases the article was published by a French team and in 18 cases from a USA team. Most frequent topics were: hepatocellular carcinoma (17 articles), liver cysts [9], major hepatectomy [8], left lateral resection [7], colorectal metastases [6], benign diseases [4] and living donor hepatectomies [3]. LLR is worldwide performed and surgical indications are expanding.